2012
DOI: 10.1083/jcb.201112094
|View full text |Cite
|
Sign up to set email alerts
|

Ovastacin, a cortical granule protease, cleaves ZP2 in the zona pellucida to prevent polyspermy

Abstract: After fertilization, the metalloendoprotease ovastacin is released by cortical granule exocytosis and cleaves the zona pellucida glycoprotein ZP2, an essential step to block sperm binding to an already fertilized egg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
260
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(269 citation statements)
references
References 42 publications
(58 reference statements)
4
260
0
Order By: Relevance
“…In fact, more recent work indicates that both purified mZP3 and mZP2 can bind to both AI and AR sperm (Kerr et al 2002). Furthermore, the supramolecular structure model of Dean et al argues that sperm would interact with both mZP3 and mZP2, provided that mZP2 is intact; only after a cleavage of mZP2 by a cortical granule protease to generate mZP2 f (Burkart et al 2012), sperm can no longer bind to the ZP (Gahlay et al 2010). Supporting the argument that the binding of mZP2 and mZP3 to sperm is a continuous event are the findings that a number of acrosomal proteins bind to the ZP (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, more recent work indicates that both purified mZP3 and mZP2 can bind to both AI and AR sperm (Kerr et al 2002). Furthermore, the supramolecular structure model of Dean et al argues that sperm would interact with both mZP3 and mZP2, provided that mZP2 is intact; only after a cleavage of mZP2 by a cortical granule protease to generate mZP2 f (Burkart et al 2012), sperm can no longer bind to the ZP (Gahlay et al 2010). Supporting the argument that the binding of mZP2 and mZP3 to sperm is a continuous event are the findings that a number of acrosomal proteins bind to the ZP (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Dean and colleagues present evidence that the supramolecular structure of the ZP, regulated by intactness of mZP2, is required for AI sperm binding (Rankin et al 2003, Gahlay et al 2010. Once mZP2 is cleaved at Ala166 to form mZP2 f , as occurring after fertilization (Burkart et al 2012), the ZP matrix becomes refractory to sperm binding (Florman & Ducibella 2006). Accumulated evidence also reveals the participation of acrosomal matrix proteins in ZP binding, a basis for how acrosome reacting sperm remain bound to the ZP (Kim & Gerton 2003, Buffone et al 2008a, 2008b.…”
Section: Introductionmentioning
confidence: 98%
“…With the penetration of the sperm into the egg, ovastacin is released from the egg's cortical granules and cleaves the zona pellucida 2 protein (ZP2) (Burkart et al 2012), leading to zona hardening and preventing polyspermy. In a recent study, ZP2 peptidetreated beads, deployed in the mouse female reproductive tract, act as a decoy to attract sperm and form binding, resulting in female infertility (Avella et al 2016).…”
Section: Fertilizationmentioning
confidence: 99%
“…These results indicated that ZP3 is the sperm binding protein in the pvm of both chicken and quail, though the detailed mechanism was not known. In mice, it was reported that ZP2 also supports the sperm binding (Bleil et al, 1988), and the structural change of the ZP2 as a result of limited digestion by the cortical granule protease protects the polyspermic fertilization (Burkart et al, 2012). In birds, ZP2 is expressed in the oocyte of immature follicles and exists in the pvm as a minor component (Kinoshita et al, 2010).…”
Section: Sperm-egg Bindingmentioning
confidence: 99%
“…protein so sperm no longer interacted with such ovastatinmodified zona pellucida in mice (Burkart et al, 2012). In the case of Xenopus laevis fertilization, soon after the entry of the first sperm into the egg, the egg's plasma membrane quickly changes to initiate a fast block to polyspermy by eliciting a positive-going fertilization potential to prevent the fusion of a second sperm (Elinson, 1986;Iwao, 2000;Wong and Wessel, 2006).…”
Section: Protease Responsible For Pvm Digestionmentioning
confidence: 99%